Teaching English as a social practice: A practical guide - Kepe, M.H.; Linake, M.A. (South African Journal of Higher Education, 2019)
Pressured into learning by rote, learners appear to fail to benefit on the joys and delights of literacy, such as initiating discussions with the teacher in class, developing critical or analytical attitudes to items around them and discovering the inter-connectedness of texts that might have been gained through reading. Since several teachers appeared to be uncertain about making their learners’ needs a focus of instruction, poetry in this study, proved to be an answer. This study focussed on how English can be taught as a social practice through a literacy process view at Devos Malan’s high school learners in King Williams Town, in the Province of the Eastern Cape in South Africa. The study employed Atwell’s Reading Workshop to collect data. The study is qualitative and interpretive. This study proposed to concentrate on three remedies of the reading workshop: Reading a book of choice with time to read in class in a chosen school; intrinsic motivation; a literacy process view and environment/ecology and; reading and sharing poetry. Foucault’s Critical Discourse Analysis as a theoretical framework, informed this study. The study reveals that no other genre can equal teaching poetry concerning diction, precise vivid words, the importance of a first-person voice, the value of all parts of speech, the beauty of figurative language and the necessity of punctuation and proper grammar.